PENGARUH KEPEMIMPINAN DAN IKLIM ORGANISASI TERHADAP KINERJA DENGAN MEDIASI KOMITMEN ORGANISASIONAL (Studi pada Keuangan KODAM IV/ Diponegoro) - Kurnia Maria Amartin, 11.4202.0023 (Students Journal of Economic and Management, 2013)
This study aims to determine whether the organization is able to mediate the effect of the commitment of the leadership and organizational climate to employee performance Kudam IV / Diponegoro, as well as to determine whether either partially or jointly, variable leadership, organizational climate and organizational commitment affect employee performance. This research was conducted with explanatory method, the research aims to prove the truth of the hypothesis that previously existed. Analysis techniques are used factor analysis to test the validity of data, analysis of Cronbach alpha test for reliability of data, regression testing, conformance model (test determinants) and mediation test to test and prove the research hypothesis. The analysis and discussion of this study demonstrate that the partial and together, the variables of leadership, organizational climate and organizational commitment in a positive and significant impact on employee performance Kudam IV / Diponegoro. Of the three variables, organizational commitment that contributed the most impact leadership variable 0.490 followed by 0.274 and the smallest contribution by organizational climate influence for 0,201. Mediation test showed that organizational commitment can only mediate the effect of organizational climate on performance, while the latter can not be mediated by leadership commitment organisasonali. These results indicate that in order to improve employee performance Kudam IV / Diponegoro, the things that need to be improved first priority is to increase organizational commitment and leadership at the agency. Â Keywords: leadership, organizational climate, organizational commitment, performance